2016
DOI: 10.7554/elife.12444
|View full text |Cite
|
Sign up to set email alerts
|

The autophagy gene Atg16l1 differentially regulates Treg and TH2 cells to control intestinal inflammation

Abstract: A polymorphism in the autophagy gene Atg16l1 is associated with susceptibility to inflammatory bowel disease (IBD); however, it remains unclear how autophagy contributes to intestinal immune homeostasis. Here, we demonstrate that autophagy is essential for maintenance of balanced CD4+ T cell responses in the intestine. Selective deletion of Atg16l1 in T cells in mice resulted in spontaneous intestinal inflammation that was characterized by aberrant type 2 responses to dietary and microbiota antigens, and by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
187
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(193 citation statements)
references
References 77 publications
6
187
0
Order By: Relevance
“…Targeted deletion of ATG16L1 in CD4+ T cells results in increased Th2 expansion and impaired Treg development leading to spontaneous intestinal inflammation. 49 Overall, induction of Atg16l1 expression by VDR 13 in intestinal epithelial cells may play a critical role in maintaining intestinal homeostasis.…”
Section: Vitamin D/vdr Regulates Immunitymentioning
confidence: 99%
“…Targeted deletion of ATG16L1 in CD4+ T cells results in increased Th2 expansion and impaired Treg development leading to spontaneous intestinal inflammation. 49 Overall, induction of Atg16l1 expression by VDR 13 in intestinal epithelial cells may play a critical role in maintaining intestinal homeostasis.…”
Section: Vitamin D/vdr Regulates Immunitymentioning
confidence: 99%
“…Similar to T MEM , regulatory T cells (T reg ) are antigen-experienced cells that maintain a state of readiness over an extended period of time that allows them to respond quickly if and when they are needed. While in this homeostatic, nonproliferative state, T reg cells switch to FAO-driven OXPHOS as main fuel source and have elevated levels of autophagy [50][51][52]. Two recent studies have shown that autophagy is indeed an essential player in T reg -cell maintenance and function by supporting their metabolic adaption and prevention of excessive glycolysis [51,53].…”
Section: T-cell Development: Autophagy and Energy Metabolismmentioning
confidence: 99%
“…While in this homeostatic, nonproliferative state, T reg cells switch to FAO-driven OXPHOS as main fuel source and have elevated levels of autophagy [50][51][52]. Two recent studies have shown that autophagy is indeed an essential player in T reg -cell maintenance and function by supporting their metabolic adaption and prevention of excessive glycolysis [51,53]. While the authors note a decrease in the terminal differentiation marker KLRG-1 in T reg cells from Atg16l1 f/f 9 foxp3-Cre mice, they conclude that autophagy deficiency mainly affects T reg -cell maintenance and survival in the context of metabolic adaptation to the intestinal microenvironment.…”
Section: T-cell Development: Autophagy and Energy Metabolismmentioning
confidence: 99%
“…S5). Further, recent reports reveal a role for autophagy components in T reg homeostasis (34, 35). Our findings indicate that ATG16L1-deficient DCs fail to respond to B. fragilis OMVs, demonstrating that autophagy components in DCs are required for commensal-driven T reg induction and function.…”
mentioning
confidence: 99%